Dual role of rVSV vectors in prophylactic and therapeutic innovation: a comprehensive bibliometric and clinical trial perspective - Chen, Yueqing; Zhang, Yongxian; Zhang, Yifei; Bie, Changwen; Wang, Runze; Zhao, Yan; Lu, Mijia (Frontiers in Immunology, 2026)
BackgroundRecombinant Vesicular Stomatitis Virus (rVSV) vector vaccines have become essential in combating emerging viral diseases and have shown promise in immunotherapy, particularly in the discipline of cancer treatment. Although extensive research has been conducted in this rVSV field, a comprehensive bibliometric and landscape analysis is lacking.ObjectiveTo depict the current research landscape of recombinant vaccines and antitumor agents based on the VSV vector, especially of the critical focus areas, emerging trends, and ongoing clinical trials.MethodsThe software CiteSpace was used to conduct the bibliometric analysis to visualize rVSV research trends, prominent authors, leading institutions, contributing countries, frequently used keywords, and the top 10 most cited articles. Additionally, the advancements and research directions were explored by analyzing active clinical trials related to the rVSV field.ResultsA total of 311 publications from 1996 to 2024 were screened out from the Web of Science Core Collection based on predefined inclusion criteria. The cumulative annual publication volume showed a steady increase, with the United States and Canada leading in research output. Notable authors such as Heinz Feldmann and John K. Rose were identified as the most frequently cited contributors. Key cluster and reference analyses revealed a shift from studying basic mechanisms to focusing on vaccine construction and clinical trials. Furthermore, efficient trials were identified in both infectious disease vaccines and antitumor agents, providing insights into potential applications in the indication expansion of currently applied vaccines and precise targeting strategies in newly developed tumor agents.ConclusionBenefited by the CiteSpace-generated bibliometric analysis, this study mapped the evolution of research and highlighted key topics in rVSV vaccine development. The comprehensive review of recent advancements and active clinical trials (using clinicaltrial.gov) offers valuable insights into current trends and future research directions.